The roles and relationships of members of the family with a functionally disabled elderly - Punzalan, Alice Hermilyn Pagala; Covar, Miriam M. (2004)
This study was to find out the roles and relationships of the members of the family with a functionally disabled elderly. Eighteen (18) functionally disabled elderly and their family members were chosen from selected hospitals in Quezon City. Data for this study was gathered through personal interviews or "pakikipagkuwentuhan" with the functionally disabled elderly in their homes. The researcher tried to know what roles and relationships, and what responsibilities they undertook to attend to the needs of their functionally disabled elderly. Through this study, the researcher also tried to know how the functionally disabled elderly felt about the caregiving of its members. results show that all members of the family regardless of where they lived, whether it be in Manila, in the province or abroad. The roles performed include purely caregiving and financial support. Also, adjustment6s and arrangements were made by family members to meet the needs of the functionally disabled elderly. Findings of the study also show that in the performance of the roles for the functionally disabled elderly, the family members encountered either physical, inner tension, psychological, or emotional stress. Furthermore, results of the study also show that both the relationships between the family members of the functionally disabled elderly family members' of the functionally disabled elderly and the families of the functionally disabled elderly's children, especially their spouses were affected in the functionally disabled elderly family members' performance of their responsibilities for the elderly. These effects include conflicts, misunderstandings, silent treatment, verbal exchanges and physical fights. I spite of the dissatisfactions that some elderly felt, it was found in the study that all the functionally disabled elderly were satisfied with the support given by the members of their family. As a whole, the study confirms the concept that roles and relationships of the members of the family with a functionally disabled elderly is embedded in the Filipino socio-cultural make-up and Filipino family values. These roles and responsibilities manifest the culture's deep family values transmitted from one family member to another. An implication of this study is the importance of parents among family members in caring for its members and maintaining good family relationships in spite of difficulties.
Thesis (M.F.L.C.D.)--University of the Philippines, Diliman.
Keywords: Aged people with disabilities -- Philippines -- Quezon City -- Family relationships; Aged people with disabilities -- Home care -- Philippines -- Quezon City; Aging parents -- Home care -- Philippines -- Quezon City; Aging parents -- Philippines -- Quezon City -- Family relationships